Temperature-Dependent Electrical Characteristics of Silicon Biristor - Eunseong Kim; Doohyeok Lim (Micromachines, 2023)
In this study, we investigate the temperature-dependent electrical characteristics of bistable silicon resistors (biristors) at temperatures ranging from 275 to 400 K. The proposed biristor exhibits low latch voltages owing to the surface accumulation layer transistor concept. Moreover, the biristor was abruptly turned on and off by positive and negative feedback phenomena, respectively. As the temperature increased from 275 to 400 K, the latch-up voltage decreased from 2.131 to 1.696 V, while the latch-down voltage increased from 1.486 to 1.637 V. Mechanisms of temperature-dependent change in latch voltage were analyzed using energy band diagrams. This temperature-dependent analysis on silicon biristor can serve as blueprint for the contribution of stable operation.